AN ANALYSIS OF STRATEGIES USED IN SUBTITLING UTTERANCES OF "THE BOURNE ULTIMATUM" - Miptahudin, - (2008)
This research paper investigates two main points. First, the strategies used in subtitling utterances of "The Bourne Ultimatum" film. Second, the strengths and weaknesses of the strategies used in subtitling the film. The research is qualitative, while descriptive method is used to analyze and process the data. To answer the research questions, the researcher uses Gottlieb's subtitling strategies. The findings shows that only eight strategies are employed by the subtitler in this film, they are; expansion, paraphrase, transfer, imitation, transcription, condensation, decimation, and deletion. Those strategies have their own strengths and weaknesses and there's no good-for-all strategy. However, it is possible to combine several strategies in order to get a better subtitle.